Enhanced levels of prostaglandin E2 and matrix metalloproteinase-2 correlate with the severity of airflow limitation in stable COPD - CHEN, Yan; CHEN, Ping; HANAOKA, Masayuki; DROMA, Yunden; KUBO, Keishi (Respirology (Carlton, Vic.), 2008)
Background and objective:  Cyclooxygenase‐2 (COX‐2) and its product prostaglandin E2 (PGE2) have been demonstrated to play critical roles in inflammation in respiratory diseases. However, the role of COX‐2 in airway remodelling in COPD remains to be elucidated. Matrix metalloproteinase‐2 (MMP‐2) is associated with both inflammation and airway remodelling in COPD. The objective of this study was to measure the expression of COX‐2 and the concentrations of PGE2 and MMP‐2, and to investigate the role of COX‐2 and PGE2 in airflow limitation mediated by MMP‐2, in the pathogenesis of COPD. Methods:  Forty‐three patients with stable COPD, twelve smoking control subjects and ten non‐smoking control subjects were enrolled. Induced sputum was obtained for measurement of the concentrations of PGE2 and MMP‐2 by ELISA. COX‐2 protein expression was assessed by western blotting. Results:  PGE2 and MMP‐2 concentrations were significantly higher in both smoking control subjects and patients with COPD than in non‐smoking control subjects (P < 0.01). Moreover, the levels of PGE2 and MMP‐2 were inversely correlated with FEV1% predicted in COPD patients (PGE2: r = −0.748, P < 0.01; MMP‐2: r = −0.801, P < 0.01). Levels of PGE2 were also positively correlated with those of MMP‐2 in patients with COPD (r = 0.775, P < 0.01). Expression of COX‐2 protein was significantly higher in COPD patients than in non‐smoking control subjects. Conclusions:  COX‐2 and its product PGE2 are not only involved in airway inflammation, but may also contribute to the severity of airflow limitation mediated by MMP‐2 during progression of COPD.